Performansi aktual modul photovoltaik dengan pengarah matahari - Jalaluddin .; Baharuddin Mire (Badan Kerja Sama Teknik Mesin Indonesia, 2017)
Actual performance of photovoltaic module with solar tracking is presented. Solar radiation can be converted into electrical energy using photovoltaic (PV) modules. Performance of polycristalline silicon PV modules with and without solar tracking are investigated experimentally. The PV module with dimension 698 x 518 x 25 mm has maximum power and voltage is 45 Watt and 18 Volt respectively. Based on the experiment data, it is concluded that the performance of PV module with solar tracking increases in the morning and afternoon compared with that of fixed PV module. It increases about 18 % in the morning from 10:00 to 12:00 and in the afternoon from 13:30 to 14:00 (local time). This study also shows the daily performance characteristic of the two PV modules. Using PV module with solar tracking provides a better performance than fixed PV module.